Women Leadership: A Comparative Study Between Indonesia and Greece - Lydia Kanelli Kyvello Kokkaliali; Ismi Dwi Astuti Nurhaeni (Jurnal Studi Pemerintahan, 2017)
One manifestation of women’s leadership is their representation in politics. Although regulation for their participation is implemented, representation in elected office is lower than anticipated. This article discusses women’s representation as leaders in strategic positions, the challenges of affirmative action regulation and the cultural barriers they face in Indonesia and Greece. The study was conducted in Indonesia and Greece, with documentation method as data collection technique such as: affirmative action regulation on women’s participation in strategic positions and official statistics of women in office. Mix methods employed for data analysis. The findings show three results. Firstly, there are differences in the representation of women as leaders both in numbers and strategic positions held between the two countries. The number of women representatives in parliament in Indonesia is lower than that of Greece, with 17 % and 20% respectively. However, the most important position obtained by a woman in Indonesia is state leader, whilst in Greece is merely minister. Secondly, both countries have implemented legislation for affirmative action regulating the percentage of women candidates. The challenge is how to ensure a raise of women representation as leaders in strategic positions. Finally, women still face cultural barriers such as stereotyping, marginalization and sub-ordination. Civic education providing skills and gender sensitivity concerning leadership for men and women can outdo the barriers. Concluding, differences of women’s leadership in Indonesia and Greece are seen in their number, position, regulation and cultural barriers. This study recommends both countries to conduct regulation concerning women’s representation, not candidacy.